2006
DOI: 10.3126/jiaas.v27i0.699
|View full text |Cite
|
Sign up to set email alerts
|

Absconding Behavior and Management of Apis cerana F. Honeybee in Chitwan, Nepal

Abstract: Twelve colonies of five-framed Apis cerana F. with about equal brood, hive storage and colony strength were prepared in November 2004 and the colony development parameters recorded. One-third of the colonies absconded in summer and about one-sixth in rainy season, while non-absconded colonies also slowed comb building, brood rearing, colony strength and hive storage in summer and rainy seasons. Feeding sugar candy and pollen substitute prevented absconding in May and July. Three weeks feeding in May resulted h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…We, therefore, decided for the elephant behavior experiment to hang A. mellifera hives on the beehive fence, as during daytime this species exhibited a slightly higher defensive reaction that increased over time. Additional economic factors played a role in selecting this species for our experiment, i.e., A. mellifera produces more honey and is easier to cultivate and manage (Verma 1991), while A. cerana has a high tendency to abscond when conditions are not favorable (Pokhrel et al 2006). In fact, two of the six initial A. cerana hives that started this study absconded before and during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, decided for the elephant behavior experiment to hang A. mellifera hives on the beehive fence, as during daytime this species exhibited a slightly higher defensive reaction that increased over time. Additional economic factors played a role in selecting this species for our experiment, i.e., A. mellifera produces more honey and is easier to cultivate and manage (Verma 1991), while A. cerana has a high tendency to abscond when conditions are not favorable (Pokhrel et al 2006). In fact, two of the six initial A. cerana hives that started this study absconded before and during the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A. cerana preparing for migration (seasonal absconding) are characterised by decreasing numbers of pollen-carrying workers, greatly reduced brood feeding and rearing, and reduced predator and parasite defence [ 6 , 15 ]. In addition, honey and pollen stores, eggs, and open and closed brood decrease dramatically, leading to large changes in colony demography [ 80 , 86 , 87 ].…”
Section: Swarming and Abscondingmentioning
confidence: 99%
“…Rainfall may impair access, increase danger, or reduced honey availability due to migration of bee colonies. Studies suggest that A. dorsata colonies migrate seasonally between nesting sites during the transition from the rainy to dry seasons and occupy nesting sites for around three to four months (Pokhrel et al ., ;). Focus group discussions revealed that periods of low income may encourage honey hunters to harvest under less favourable conditions, such as times with low honey yields or before the honey is ripe.…”
Section: Resultsmentioning
confidence: 99%